Analysis of mixing coal and biomass fuels on industrial boiler performance - Chin, Jacky (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2024)
The aim of this study is the experimental investigation and characterization of the effects of using biomass mix and coal fuels boilers on the efficiency and environmental impact of industrial boiler combustion. The experimental data collected relates to the coal boiler and biomass mix fuel boiler, and boiler performance parameters. Two different methods for controlling coal and biomass mix fuel feed are considered. One method involves manually controlled biomass mix feed through the boiler control system and one more for use full coal boiler. The boilers control system regulates the intake of coal and biomass mix fuel into the furnace based on combustion chamber temperature and pressure parameters. The results shows that the biomass mix boiler does not significantly affect the combustion process but reduces fuel consumption, better than coal boiler. The findings are expected to provide valuable insights for industry stakeholders and policymakers, promoting the adoption of more sustainable and cost-effective fuel alternatives in industrial applications.